Technological Innovation : Concepts for Economy Driving in an Era of Platform Economy - Ieamvijarn, Subunn (Journal for Developing the Social and Community, 2022)
The development of Thailand in an era of platform economy focus on creating economic which is driven by technological innovation and creativity thinking. Businesses can bring products and services into the online platforms. Also, it can reach more customers, convenient transaction and faster on both the seller and the customer including create a competitiveness. This academic paper purposes technological innovation as concepts for economy driving in an era of platform economy and the guidance for country development with the aim for growth and sustainability in the future.